(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A nail is a structure which is not a bone made up of different composition than skin tissue like keratin which is also found in hair and this is also shown as an outer layer of skin for protection. Nail used to protect finger tips and surrounding tissues from injury. The epithelial matrix cells adhering to the nail bed give rise to the development of nails. There is a difference between healthy and unhealthy nails which is recognizable by their difference in color, healthy nails are pink in color and have a flexible smooth and glossy surface of nail. When it comes to growth the development of nails is an indication of eliminating dead cells from the human body. The growth rate of nails are higher in children than young and elderly adults. Human nails and issues connected with it such as size, color and form of the nail will also reveal the kind of illness and problems associated with the body. Human nails consist of numerous components which have been described in this article and also nails utilized to accomplish different jobs are also detailed in this paper. Human nails may act as an indication and it is a very useful method for the treatment of various illnesses. In this paper also discussed the purpose of the study which is to measure the ph level of the nail and maintain healthy nail, to maintain the healthy nail we have to measure the ph level of nail paint and other nail related chemicals so that it can give a healthy and shiny nail plates, in this paper on the basis of healthy ph value of nail plate people can control the flow of nail paint and nail paint remover on it. Also, the scope of the invention and why taking care of nail and nail related treatments and issues has been addressed in this paper, how we can maintain or raise or reduce the PH level of nail has also been mentioned in this paper.